Strategi pemasaran melalui media sosial dalam meningkatkan penjualan usaha mikro kecil menengah di Jawa Barat: Studi literatur sistematis - Fauzan, Rafi Muhammad (Journal of Management and Digital Business, 2025)
This article analyzes how micro, small, and medium-sized enterprises (MSMEs) can produce effective, high-quality social media content to compete with larger companies. The review focuses on the use of digital technology to increase brand awareness, strengthen promotion through engaging content, and support marketing decisions, including the choice of selling locations. The discussion centers on MSMEs operating in West Java, Indonesia. Using a literature review approach and the 4P marketing mix framework (product, price, place, and promotion), the study identifies relevant content strategies and social media marketing practices. The findings indicate that the strategies most consistently associated with higher sales include producing informative and attractive content, engaging directly with consumers through live-streaming features, and using customer feedback to improve products and services. However, the review is largely limited to literature emphasizing content strategies and does not examine in depth the practical implementation barriers MSMEs face in the field.